Boikot Produk Unilever: Adakah Dampaknya Terhadap Return Saham PT Unilever Indonesia? - Fitriza Rahma; Anwar, Azwar; Oktaviyah, Nurafni (Jurnal Iqtisaduna, 2024)
The boycott campaign, actively promoted by the predominantly Muslim population in Indonesia, is seen as a form of solidarity with the Palestinian people and a response to the Indonesian Ulema Council (MUI) Fatwa Number 83 of 2023. This campaign has led to a decline in stock prices and returns for the targeted companies. This article aims to examine the impact of the boycott campaign against Unilever products on the stock returns of PT Unilever Indonesia before and after the issuance of MUI Fatwa Nmber 83 on November 8, 2023, which serves as the event date (t-0). A quantitative comparative approach was employed using time series data and probability sampling methods, specifically systematic sampling. The sample consists of weekly closing stock prices from observation windows ranging from t-30 to t+30, t-20 to t+20, and t-10 to t+10 around the event date. Data analysis was conducted using statistical tests, including normality tests, paired sample t-tests, and wilcoxon signed-rank tests. The results indicate no significant differences during the analyzed periods, suggesting that the boycott campaign had no substantial effect on stock returns before and after the issuance of MUI Fatwa Number 83 of 2023. This reflects the strength of brand loyalty, the stability of the Fast Moving Consumer Goods Industry, and market perception that remains unaffected by the negative signals from the boycott.